STUDI ETNOBIOLOGI BAHAN OBAT-OBATAN PADA MASYARAKAT SUKU TAA WANA DI DESA MIRE KECAMATAN ULUBONGKA KABUPATEN TOJO UNA UNA SULAWESI TENGAH - Muhammad Akhsa; Ramadhanil Ramadhanil; Syariful Anam (Biology Department, Mathematics and natural science, Tadulako University, 2015)
A research entitled “Ethnobiological Study of Medicinal Material in the Taa Wana Community in Mire Village, Ulubongka, Tojo Una Una District Central Sulawesi” has been conducted from September to October 2014. The research objective was to obtain the information of Plants and Animals diversity and its part that utilized as traditional medicine. The research was done by using semi structure interview technique to 24 respondents with quisioner sheet. The result showed that there were fourty (40) plants species and fourteen (14) animals species that used by the Taa Wana Community in the studied area. The highest percentase that used in the part of plants were 60% of leaves and 43% part of meat of the animal. The type of the illness that can be threated are chronic, infections, non-communicable and also to health care. Keywords : Taa Wana Ethnic, Mire Village, Tojo Una Una Central Sulawesi, Ethnobiology